Analysis of the reinforced concrete columns concealing rain water pipe in multi-storey buildings. - Bakhteri, Jahangir (Universiti Teknologi Malaysia, 2004)
Reinforced concrete columns concealing PVC drain water pipe have been used widely in the construction of multi storey buildings. The purpose of the investigation is to study thedeficiencies caused in the strength and load carrying capacity of these columns through experimental and numerical analyses. A total number of 28 columns have been cast and only the appropriate ones which were without defects, have been tested under the axial compressive load. An approximate method of alignment for constructed columns has been developed and the alignment of the alignment of the columns has been carried out before their testing. The study shows these columns have huge reduction in their load carryingcapacities. The investigation showed that concealing drain pipes inside these columns had significant effects on their strength and mode of failure. Three-dimensional finite element analysis of the above mentioned columns have also been carried out to investigate the effects of drain pipes on load carrying capacities of the columns. The numerical investigation predicts higher factors of safety than the experimental results. In conculsions, the factors of safety obtained from experimental study shows that, the performance of the columns are in a critical level and could be hazardous to the safety of the building. Therefore, an improved method of positioning the drain pipes outside the columns as well as the replacement of the PVC pipes by steel has been proposed.